Study of corrosion behaviour of steel reinforcement in fibre-reinforced concrete - Lim, Jun Jie (2015)
Concrete cracking in steel reinforced concrete structures reduce the lifespans on these structures and require large amounts of money to repair and retrofit. To remedy this problem, there have been proposals to use fibre-reinforced concretes such as the Engineered Cementitious Composites (ECC) that are a class of ultra-ductile fibre-reinforced concrete as a construction material. This project aims to investigate the corrosion behaviour of the steel reinforcements in such fibre-reinforced concrete undergoing accelerated corrosion through the use of corrosion tests like the Linear Polarization Test (LPR), Tafel test and the Electrochemical Impedance Spectroscopy to determine the corrosion parameters of the reinforcements at various points in time. The mass loss of the reinforcements was also calculated to determine the mass loss rate of the samples. Microscopic investigations of the samples were conducted with the use of the optical microscope and the Scanning Electron Microscope to determine the distribution, morphology and degree of crystallization of the rust crystals. It was found that the confinement effect of the ECC samples occur only in the samples with at least 1% fibre content and becomes evident only when a certain degree of corrosion has occurred. This confinement effect was also found to improve the corrosion resistance of the samples and this effect was further reinforced by the mass loss results in which mass loss rates decreased with increasing fibre content.